MEDICAL SOCIAL ASPECTS OF MATERNAL MORTALITY IN YOUNGER WOMEN IN THE RUSSIAN FEDERATION - E.V. Guseva; O.V. Chumakova; O.S. Filippov ("Paediatrician" Publishers LLC, 2008)
The structure and causes of maternal mortality in younger women (n = 50) in the Russian federation in 2002-2006 years was analyzed. About 8% of women died before 28 week of pregnancy, 66% of women died during labor and in postpartum period, cause of death in 26% of patients was the abortion before 28 week of pregnancy. The most frequent causes of maternal mortality in younger women are gestosis (in 30% of patients), extragenital diseases (in 26% of patients), and septic complications (in 20% of patients). The quality of medical care was analyzed. Proved, that interaction between obstetrician gynecologist and pediatricians, psychologists and social workers and prophylaxis of unwanted pregnancy in adolescents is essential to prevent maternal mortality in younger women. Prophylactic measures must be directed to active pregnancy finding in young women, early registering, and close observation and following delivery in perinatal centers or specialized maternity hospitals. Key words: younger women, maternal mortality, prophylaxis.